Evaluation of Patients' Recovery from Hepatitis C Following Antiviral Treatment with Daclatasvir and Sofosbuvir in AL-Baha Region - Fahad Alghamdi; Rashed Mohammed (International Journal of Advanced Humanities Research)
The liver is the largest organ in the body, located below the diaphragm and protected by the lower ribs of the rib cage (Johns Hopkins Medicine, 2022). Many hepatitis viruses infect the liver, among them Hepatitis C, which currently has no effective vaccination (Lazarus et al., 2020; Park & Hahn, 2023; David et al., 2007). After infection, the patient usually receives daclatasvir and sofosbuvir for 12 weeks (Cheema et al., 2019). A comprehensive examination of liver function tests is essential for the clinical management of liver diseases, especially for tracking infection elimination and determining the efficiency of medicinal treatments (Sharma & Nagalli, 2022; Newsome et al., 2018; Belforte et al., 1985). Among those tests are liver enzyme alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (World health organization, 2022). This study will assess liver function enzymes ALT and AST of patients infected with the hepatitis C virus before and after the treatment. Those patients were confirmed to be infected by PCR analysis in the Al Baha region. The patients' data and enzyme profiles were obtained from the general directorate of health affairs in the Al Baha region, the Ministry of Health, and the SANED Platform